Modulation of Human Immune Response by Fungal Biocontrol Agents - Konstantinovas, Cibele; de Oliveira Mendes, Tiago A.; Vannier-Santos, Marcos A.; Lima-Santos, Jane (Frontiers in Microbiology, 2017)
Although the vast majority of biological control agents is generally regarded as safe for humans and environment, the increased exposure of agriculture workers, and consumer population to fungal substances may affect the immune system. Those compounds may be associated with both intense stimulation, resulting in IgE-mediated allergy and immune downmodulation induced by molecules such as cyclosporin A and mycotoxins. This review discusses the potential effects of biocontrol fungal components on human immune responses, possibly associated to infectious, inflammatory diseases and defective defenses.